Upaya Pencegahan dan Pemberantasan Korupsi Melalui Pendidikan Anti Korupsi di Perguruan Tinggi - Ni Nyoman Rini Permatasari (Ganesha Civic Education Journal, 2022)
Today the crime of corruption is starting to run rampant, corruption is now not only in the scope of government but also penetrates the world of education. Corrupt behavior that continues to accumulate in society will have an impact on the younger generation. The younger generation is the next generation of the nation who will continue the life of government. If this corrupt behavior grows in the younger generation, this act of corruption will not be interrupted and will continue to grow so that it will destroy the Indonesian nation itself. One of the implementation of corruption prevention efforts is through anti-corruption education in universities. The learning process in anti-corruption education is to strengthen students' deepening of anti-corruption education so that students are taught to behave critically in situations of acting or behaving according to anti-corruption values. As well as the importance of the role of tertiary institutions as a place to carry out efforts to prevent and eradicate corruption. In writing this article, the author uses a qualitative approach with the library study method, in which the sources are used as a study in describing efforts to eradicate and prevent acts of corruption through anti-corruption education from various studies that are used as comparisons, namely references to articles, journals, books, and media. -print and electronic media as well as sources of other research studies.